Promotion In Automobile Company - Sakandar Khan, Hamidah (2007)
At Honda Malaysia as in the other regional Honda offices, efforts have been to develop an internal promotion standard that is flexible, fair and responsive enough to respond to the internal labor market forces towards the selection of the most qualified personnel for promotion.